Inhibition effect of naturally occurring metal-binding compounds on the microbiologically influenced corrosion of mild steel - Dubey R.S.; Upadhyay S.N. (My University, 2025)
The corrosion behaviour in the presence of immobilized and streptomyces griseus was measured by weight loss, corrosion potential and potentiodynamic polarization techniques. The observed inhibition of mild steel in presence of immobilized p.fluorescens and streptomyces griseus was attributed to the production of antibiotics such as oxopolyene macrolides which act as good inhibitors and chemisorbed onto the surface of mild steel. © 1999 CECRI.